(497) Analytical Study of the Relationships Between Consumption Expenditure On Different Groups of Commodities & Total Annual Consumption Expenditure for The Household Sector Urban and Rural Regions دراسة تحليلية للعلاقات بين الإنفاق الاستهلاكي على مجموعات مختلفة من السلع وإجمالي الإنفاق الاستهلاكي السنوي للقطاع المنزلي في المناطق الحضرية والريفية - Madany D. Mostafa, Moharram W. Mahmoud (معهد التخطيط القومي, 2026)
This study investigates the relationships between household consumption expenditure on different commodity groups and total annual consumption expenditure in urban and rural regions. The primary objective is to explain consumption behavior and identify how expenditure patterns respond to changes in total household expenditure levels. The analysis relies on data obtained from the Family Budget Survey conducted between November 1958 and October 1959 while considering regional differences and household characteristics such as family composition, age structure, and demographic variation. The study employs a quantitative statistical approach through the estimation of mathematical functions describing the relationship between expenditure shares allocated to commodity groups and total annual household expenditure. Linear, logarithmic, and quadratic models are applied according to the statistical characteristics of each commodity category. The analysis covers a wide range of commodity and service groups, including cereals and starches, meat and fish products, milk and dairy products, vegetables, fruits, clothing, education, health expenditure, transportation and communication services, and other household expenditures. The findings indicate substantial differences between urban and rural consumption structures. Essential goods such as cereals and starches exhibit declining expenditure shares as total consumption increases, supporting Engel’s Law, whereas expenditures on education, medical services, transportation, durable goods, and other services increase with higher consumption levels. The study also demonstrates significant differences in elasticity coefficients across commodity groups, reflecting variations in the responsiveness of consumer demand to economic changes. The study concludes that expenditure function analysis provides an effective framework for understanding household consumption behavior and forecasting future needs. Furthermore, it contributes to economic planning and supports policy formulation